2020
DOI: 10.1101/2020.03.29.014720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alzheimer’s disease risk geneBIN1induces Tau-dependent network hyperexcitability

Abstract: Genome-wide association studies identified the BIN1 locus as a leading modulator of genetic risk in Alzheimer's disease (AD). One limitation in understanding BIN1's contribution to AD is its unknown function in the brain. AD-associated BIN1 variants are generally noncoding and likely change expression. Here, we determined the effects of increasing expression of the major neuronal isoform of human BIN1 in cultured hippocampal neurons. Higher BIN1 induced network hyperexcitability on multielectrode arrays, incre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 80 publications
(82 reference statements)
1
12
0
Order By: Relevance
“…BrainPhys media (Stem Cell Technologies) was used instead of Neurobasal for media changes on DIV4 (with addition of Ara-C) and DIV9. At DIV 12, neurons were recorded on an Axion system as described previously (97). Neurons were recorded for 20 minutes for a baseline recording, then 50 uM NMDA was applied and neuronal firing was recorded for 20 more minutes.…”
Section: Multielectrode Array (Mea)mentioning
confidence: 99%
See 1 more Smart Citation
“…BrainPhys media (Stem Cell Technologies) was used instead of Neurobasal for media changes on DIV4 (with addition of Ara-C) and DIV9. At DIV 12, neurons were recorded on an Axion system as described previously (97). Neurons were recorded for 20 minutes for a baseline recording, then 50 uM NMDA was applied and neuronal firing was recorded for 20 more minutes.…”
Section: Multielectrode Array (Mea)mentioning
confidence: 99%
“…Neurons were recorded for 20 minutes for a baseline recording, then 50 uM NMDA was applied and neuronal firing was recorded for 20 more minutes. Electrical activity was analyzed with Plexon Offline Sorter and NeuroExplorer to determine action potential frequency as described previously (97). Neurons were defined to be in depolarization block if there were zero action potentials in the last five minutes of recording after NMDA application.…”
Section: Multielectrode Array (Mea)mentioning
confidence: 99%
“…BIN1 may contribute to the regulation of neuronal and circuit activity through numerous mechanisms, including increased APP processing and production of amyloid-beta peptides (Miyagawa et al, 2016;Ubelmann et al, 2017), alterations in Tau phosphorylation and propagation (Calafate et al, 2016;Lasorsa et al, 2018;Sartori et al, 2019;Voskobiynyk et al, 2020), subcellular localization of voltage-gated calcium channels (Hong et al, 2010;Voskobiynyk et al, 2020) and recycling of synaptic vesicles/AMPA receptors (Schürmann et al, 2019;De Rossi et al, 2020). Accordingly, conditional deletion of BIN1 in neurons of the adult mice hippocampus, leads to altered frequency of mini excitatory post-synaptic currents (mEPSC), likely due to an impaired presynaptic release probability and slower depletion of neurotransmitters (De Rossi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The BIN1 gene encodes the nucleoplasmic adaptor protein BIN1, which is predominantly expressed in brain and muscle tissue 6 and is involved in the regulation of membrane curvature, 7 clathrin‐mediated endocytosis, 8,9 presynaptic vesicle release, 10 and neuronal excitability 11,12 . Previous pre‐clinical, 8,9,13 post mortem , 13–15 and biomarker studies 8,16,17 demonstrated BIN1 involvement in the development of tau pathology, which is considered a major driver of neurodegeneration 18 and cognitive decline in AD 19 .…”
Section: Introductionmentioning
confidence: 99%